The influence of product quality and customer trust on customer satisfaction at PT. Anugrahbuah Abadi Medan - Anjelina, Anjelina; Arwin, Arwin; Yuliana, Yuliana (Journal Arbitrase : Economy, Management and Accounting, 2024)
PT AnugrahBuah Abadi is located on Jl. Platina 7 no 16,17,18,19, Kec. Medan Deli, Medan City, North Sumatra 20226, Indonesia. PT AnugrahBuah Abadi is engaged in the distribution sector selling imported and exported fruits. The company is unable to achieve sales targets and sales levels tend to decline in 2021. Employees also interact less with consumers via telephone. During this pandemic, consumers reduced their demand so that sales levels were low. The purpose of this study is the effect of product quality and consumer confidence on consumer satisfaction with sales at PT AnugrahBuah Abadi. The type of data used by researchers in this study are: quantitative data. The samples used were 30 customers of PT. AnugrahEternal Fruit. Multiple linear regression is a linear relationship between two or more independent variables (X) and the dependent variable (Y). The result of this research is that product quality has an influence on customer satisfaction at PT AnugrahBuah Abadi. Consumer trust has an influence on customer satisfaction at PT. AnugrahEternal Fruit. Product quality and customer trust affect customer satisfaction at PT AnugrahBuah Abadi